Effects of mixtures from selected functional foods hypercholesterolaemic rats - Mohd Rosmi, Noor Syafiqa Aqila (2020)
The efficacy in cholesterol treatment by mixtures from selected functional foods (MSFF) including nattokinase (fermented soybean), red yeast rice extract, Ginkgo biloba, oat fiber, garlic, bee pollen and propolis in Sprague Dawley rats. This study was to determine the cholesterol-lowering effects in MSFF on the identification of bioactive compounds, enzymatic activities (HMGCoA reductase and ACAT2), lipid peroxidation (serum and tissue MDA), histopathological analysis of liver tissue, and biochemical profiles. The rats were divided into two groups (normal control (NC) and high cholesterol fed rats (HCD) for initial 4 weeks. After 4 weeks on high cholesterol diet, the group were divided into five groups: 1% HCD, 1% HCD + Simvastatin (10 mg/kg of body weight (BW)), 1% HCD + MSFF (50 mg/kg/BW), 1% HCD + MSFF (100 mg/kg/BW) and 1% HCD + MSFF (200 mg/kg /BW). LC-MS/MS analysis showed MSFF contained Monacolin K, naringin, tocopherol and glutamate. Changes of body weight and average feed intake/week were observed for all hypercholesterolaemic rats after four weeks of treatment compared to normal group. MSFF at 200 mg/kg/BW provide a significant (p<0.05) greatest inhibition activity of 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCoA reductase) (167.86 ± 5.54 pg/ml) and acetyl-Coenzyme A acetyltransferase 2 (ACAT2) (360.19 ± 44.11 pg/ml) than 1% HCD. Lipid peroxidation showed a significant decreased (p<0.05) in serum (3.82 ± 0.83 μmol/L) and liver tissues (15.24 ± 1.81 μmol/mg) of malondialdehyde (MDA) against hepatic steatosis. MSFF at 100 mg/kg/BW had significantly (p<0.05) decreased serum total cholesterol (TC) (1.35±0.09 mmol/L) whereby MSFF at 50 mg/kg/BW reduced low density lipoprotein (LDL) (p<0.05)at 0.52 ± 0.09 mmol/L. Serum liver profiles of aspartate aminotransferase (AST) (115.33 ± 8.69 U/L) and alanine aminotransferase (ALT) (61.00 ± 1.00 U/L) were decreased significantly (p<0.05) by MSFF at 200 mg/kg/BW. These combination of functional foods ingredients could provide health-promising effect for hypercholesterolaemia.